Factors Associated With Chlamydia and Gonorrhea Treatment Completion Among Sexual Health Clinic Patients, Baltimore City, Maryland; 2018 to 2019. Issue 5 (13th May 2023) - Stracker, Norberth; Williford, Sarah L.; Gilliams, Elizabeth; Rives, Sarah; Page, Kathleen R.; Hamill, Matthew M.; Greenbaum, Adena; Schumacher, Christina M.
Abstract : Among urban sexual health clinic patients, 1 in 3 female patients and 1 in 6 male patients with chlamydia/gonorrhea were untreated. Few patient-level characteristics were associated with treatment completion, underscoring the need for point-of-care testing. Abstract : Background: Prompt and appropriate treatment of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) is critical to prevent transmission and serious sequelae. The objectives were to determine the prevalence of CT/NG treatment completion and identify demographic, behavioral, and clinical factors associated with treatment completion at sexual health clinics in Baltimore City, Maryland. Methods: Electronic health record data from patients diagnosed with CT/NG during 2018–2019 were analyzed. Treatment completion was defined as documentation of Centers for Disease Control and Prevention–recommended treatment ≤30 days after testing. Regression was used to assess differences in treatment completion across groups; analyses were stratified by birth sex. Results: Most of the 2426 male (86%) and 754 (72%) female patients diagnosed with CT/NG completed treatment in ≤30 days; 74% of male and 36% of female patients were treated same-day. Among 890 male patients not treated same-day, treatment completion was associated with other same-day antimicrobial treatments (adjusted prevalence ratio, 0.76 [95% confidence interval, 0.61–0.94]), longer test processing times (≥10 days; 0.78 [0.65—0.95]) infection at multiple anatomic sites (1.49 [1.25–1.76]), and patients with previous clinic visits (1.16 [1.03–1.31]). Among 483 female patients not treated same-day, treatment completion was associated with diagnosis year (2019 vs. 2018; 1.23 [1.05–1.43]) and residential addresses 2 to 5 miles (vs. <2 miles) from clinic (1.25 [1.02–1.53]). Demographic and behavioral characteristics were not associated with treatment completion. Conclusions: Substantial proportions of male and female sexual health clinic patients did not complete treatment. Our findings underscore the need for implementation of highly sensitive and specific point-of-care (POC) CT/NG testing to improve treatment completion in this setting.